The Best Damn Sales Book Ever: 16 Rock-Solid Rules for Achieving Sales Success! (Hardcover) - Greshes Warren (Untied States : Wiley, 2006)
The big secret to sales success? A simple truth: Motivated, positive, goal-oriented people are usually the ones who sell the most. Even if you don’t think you have these vital qualities, you can develop them in yourself — with the right help. (Realtor Magazine, July 2006)
Keywords: Sales personnel; Selling; Success in business